2007
DOI: 10.1016/j.neuropharm.2007.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Decreased withdrawal symptoms but normal tolerance to nicotine in mice null for the α7 nicotinic acetylcholine receptor subunit

Abstract: Withdrawal symptoms are a major deterrent when people try to quit smoking. The α7 subunit of the neuronal nicotinic acetylcholine receptor (nAChR) is highly expressed in the brain, and has been suspected to play a major role in nicotine addiction. We studied the influence of α7-containing nAChRs on nicotine withdrawal and tolerance, in wild type mice and mice null for the α 7 nAChR subunit (α7 −/−). For withdrawal experiments, animals were implanted with osmotic minipumps delivering nicotine for 13 days. A sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 45 publications
3
78
0
1
Order By: Relevance
“…In contrast, the somatic symptoms of nicotine withdrawal are present in both β2 KO and WT mice, suggesting that the somatic symptoms of nicotine withdrawal are mediated by other nAChR subunits [7,77,146]. Research with other nAChR subunit KO mice has demonstrated that the β4 [146], α5 [77], and α7 nAChR subunits [148] likely mediate the somatic symptoms of withdrawal. Thus, these studies provide evidence that the various symptoms of nicotine withdrawal are mediated by different nAChR subunits.…”
Section: The β2 Nachr Subunitmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the somatic symptoms of nicotine withdrawal are present in both β2 KO and WT mice, suggesting that the somatic symptoms of nicotine withdrawal are mediated by other nAChR subunits [7,77,146]. Research with other nAChR subunit KO mice has demonstrated that the β4 [146], α5 [77], and α7 nAChR subunits [148] likely mediate the somatic symptoms of withdrawal. Thus, these studies provide evidence that the various symptoms of nicotine withdrawal are mediated by different nAChR subunits.…”
Section: The β2 Nachr Subunitmentioning
confidence: 99%
“…Investigations of nicotine withdrawal symptoms have demonstrated that α7 nAChRs play a role in withdrawal-related changes in somatic symptoms and hyperalgesia [59,77,148], but do not play a crucial role in other withdrawal symptoms. Salas and colleagues [148] reported that somatic signs during nAChR antagonist-precipitated withdrawal are reduced in α7 KO mice relative to WT littermates.…”
Section: The α7 Nachr Subunitmentioning
confidence: 99%
See 1 more Smart Citation
“…The α7 nAChRs participate in auditory sensory gating, defects in which contribute to the attention and cognitive problems associated with schizophrenia [8,9]. They are also involved in the mechanism of nicotine addiction [10]. The α7 nAChR subunit, which forms robust functional homomeric receptors, has been proposed as a candidate target for new drugs designed to ameliorate symptoms of Alzheimer's disease and schizophrenia as well as to control pain [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of the α7 nAChR subunit, its deficiency results in viable, anatomically normal α7-null mice (Orr-Urtreger et al 1997;Paylor et al 1998). The only abnormal CNSrelated phenotypes reported in these mice were mild cognitive deficits (Young et al 2004(Young et al , 2007 and reduced nicotine withdrawal symptoms (Salas et al 2007). It has been suggested that overexpression of other types of nAChRs compensates for the depletion of α7-nAChRs, and in fact, the upregulation of α3 and α4 nAChR subunits was demonstrated in brains of postnatal α7−/− mice (Yu et al 2007).…”
Section: Discussionmentioning
confidence: 95%